Progesterone Therapy Administered 24 hours Before Embryo Transfer in ICSI Cycle Improves Embryo Implantation and Pregnancy in Women With Luteal Phase Defect. - Ridhaa, Mundhir T.; AL-Anssari, Saeeda A.; Kanan, Zuher; Allow, Ahmed K.; Khounda, Sarmed S. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Ovulation induction by human menopausal gonadotrophin (HMG) results in temporal luteal phase defect. Luteal support therapies are required to support embryo implantation in stimulated cycle especially in luteal phase defect infertile women. Objective: The objective of the present study was to investigate the clinical significance of progesterone, aspirin and HCG on human embryo implantation in women with luteal phase defect following ICSI and embryo transfer (ET). Patients and Methods: The female patients were divided into six groups depending on the type of the luteal support protocols (LSP). Group 1 (No= 54), received 10 mg oral progesterone (P), group 2 (No= 35) received P plus HCG, group 3 (No= 59) received P plus HCG plus oral aspirin, group 4 (No= 47) received vaginal P administered 24 hours before embryo transfer plus oral aspirin, group 5 (No= 40) received vaginal P administered 12 hours after embryo transfer plus oral aspirin and group 6 (No= 46) received intramuscular P plus oral aspirin. The LSP were continued for at least 12 weeks, when the BHCG test was positive, (tested two weeks after embryo transfer). Results: Statistical analysis of the clinical data showed no significant differences between the LSP in regard to patient’s age, body mass index (B/M2), basal FSH/LH ratio and estradiol concentration at the day of HCG injection. The ICSI rate, percentages of embryos developed in vitro, and the numbers of the transferable quality embryos were similar in all groups (P>0.05). The pregnancy rate was significantly higher (P < 0.05), in group 4 compared to other groups (38.66% versus 24.51%(G 1), 22.53% (G 2), 28.66% (G 3), 25% (G 5), 21.60% (G 6). The percentages of viable fetal sac development per patient were 31.49 (17/54), in G 1, 42.86 (15/35), in G 2, 49.16 (29/59), in G 3, 59.58 (28/47), in G 4, 32.50 (13/40), in G 5, and 34.79 (16/46), G 6. The percent of viable gestation sac was significantly higher in group 4 compared to other groups (P < 0.05). Concl u s i o n s : The administration of 400 mg /day vaginal progesterone 24 hours before ET and 100 mg/day aspirin five days after ET results in significant improvements in pregnancy and embryo implantation rates and development of viable fetuses in luteal phase defect infertile women undergoing ICSI-ET.